THE LINGUISTIC VALUE OF SLOGAN IN PANGKALPINANG CITY PUBLIC SPACE: EDUCATIONAL PERSPECTIVE - Wijayanti, Nurvita; Restu Wilujeng, Panggio (Faculty of Social and Political Sciences University of Bangka Belitung, 2019)
Nowadays, slogans in the public space have become the most significant socialist symbols and meanings that are easily accessible to the public, such as the example of writing traffic signs, billboards, information boards and other media. The problem lies in the lack of attention to the linguistic element, considering that the media contains formal slogans as a reflection of the level of standardization in the interpretation of symbols and meanings aimed at educating the public. These errors are found in a number of public spaces in Pangkalpinang City. This study aimed to describe the linguistic aspects of writing slogans in the public space as well as how to socialize about the delivery of symbols and meanings in the writing. This study also looked at how the purpose of informative education through symbols and meanings of the writing in the socialization media was interpreted by the people of Pangkalpinang. So that there are two formulations of the problem that will be elaborated in this study, namely: (1) How is the distribution of slogans in public spaces indicated to violate linguistic values ​​?; (2) How is the dissemination of symbols and meanings contained in the slogans conveyed educatively to the public? The theory used to carry out this research is the socio-phonological theory, ambiguity, and sociology of communication from Hebert Mead about symbolic interactionism. The method used was descriptive qualitative using data collection techniques, namely full observation and interviews. This research showed that there are no concepts that are misleading in conveying symbols and meanings contained in slogans in public spaces that should be formally informal because the Pangkalpinang community translates phonemes into orthographical (writing).